Negative regulation of NEP expression by hypoxia. Issue 7 (8th November 2012) - Mitra, Ranjana; Chao, Olivia S.; Nanus, David M.; Goodman, Oscar B.
Abstract: BACKGROUND: Neutral endopeptidase (NEP) is a transmembrane cell surface peptidase present on prostatic epithelial cells that catalytically inactivates small peptide substrates. Neutral endopeptidase loss is associated with prostate cancer growth, progression, and increased angiogenesis. We examined whether NEP expression is regulated by hypoxia, frequently encountered in the tumor microenvironment. METHODS: NEP expression was compared in prostate cancer cell lines cultured in normoxic and hypoxic conditions. The NEP activity, protein levels, and mRNA levels were determined using enzyme assay, Western blotting and q‐PCR analysis, respectively. Electrophoretic mobility shift assay and chromatin immunoprecipitation assay (ChIP) was used to confirm the negative regulation of NEP at the transcriptional level by hypoxia responsive elements (HREs). RESULTS: The results indicate that NEP expression was inhibited under hypoxic conditions in the NEP positive LNCaP, C4‐2, and 22RV1 cells and human umbilical vascular endothelial (HUVEC) cells. NEP regulation appeared to be predominantly at the transcriptional level as NEP mRNA expression significantly reduced with hypoxia, concordant with the kinetics of protein levels, and NEP enzyme activity. A search of the NEP gene sequence revealed three putative HREs upstream of the NEP promoter. Two of the HREs demonstrated a specific reduction of shift in the presence of cobalt chloride; specificity of the binding sites was confirmed by ChIP. CONCLUSIONS: Our data indicate a novel mechanism where hypoxia negatively regulates the tumor suppressor function of NEP in prostate cancer. The negative regulation of NEP is mediated by binding of the HIF1‐α protein binding to the HREs present upstream of the NEP promoter. Prostate 73: 706–714, 2013. © 2012 Wiley Periodicals, Inc.